EFEKTIVITAS EDUKASI KESEHATAN BERBASIS KOMUNITAS TENTANG LEPTOSPIROSIS TERHADAP PENGETAHUAN DAN PERILAKU MASYARAKAT DI KELURAHAN NEGLASARI RW 04: Efektivitas Edukasi Kesehatan Berbasis Komunitas Tentang Leptospirosis Terhadap Pengetahuan Dan Perilaku Masyarakat Di Kelurahan Neglasari RW 04 - Utami, Sekar Widya Noer; Wijoyo, Eriyono Budi; Winahyu, Karina Megasari (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2026)
Leptospirosis is a zoonotic disease that remains a major public health problem globally, particularly in areal with high rainfall, poor sanitation, and densely populated settlements. These conditions increase the risk of leptospirosis transmission, especially in high-risk urban communities such as Neglasari RW 04. This study aimed to assess the effectiveness of community-based health education on knowledge and preventive behavior toward leptospirosis. A pre-experimental design with a one-group pretest–posttest approach was applied among residents of RW 04, Neglasari. A total of 22 respondents were selected using total sampling. The education was delivered through lectures using PowerPoint, discussions, question-and-answer sessions, and leaflets. Knowledge and preventive behavior were measured using a 13-item questionnaire before and after the intervention. The results showed that before the education, most respondents had low levels of knowledge and preventive behavior, whereas after the education, 17 respondents demonstrated an increase in correct answers. These findings indicate that community-based health education plays an important role in improving public awareness and understanding of leptospirosis. Structured and locally relevant health education can serve as an effective promotive and preventive strategy for leptospirosis at the community level.